China–US Cooperation in Higher Education: A Critical Stabilizer - Postiglione, Gerard A.; Simon, Denis (International Higher Education, 2018)
The world’s two leading economies have hit a rough patch that has begun to spill over into their 40 years of cooperation in higher education. At stake is the ability of their universities to be instruments of global integration, mutual understanding, and geopolitical stability.